Preliminary assessment of the geothermal potential of Rosario de la Frontera area (Salta, NW Argentina): Insight from hydro-geological, hydro-geochemical and structural investigations - Invernizzi, Chiara (2014)
This work is part of a project aimed to the development and application of hydrogeological, hydrogeochemical and geological methodologies for the study of the geothermal system of Rosario de La Frontera (NW Argentina).The surface thermal manifestations of this area, whose temperatures range from 22.6 to 92.6°C, are mainly located in the northern sector of Sierra de la Candelaria anticline. This regional structure crops out between the provinces of Salta and Tucuman (NW Argentina), at the foothills of the central Andean retro-wedge.The present investigation focuses on hydrogeological and structural data, and isotopic compositions (18O, D and 3H) of thermal springs.Preliminary results allowed to define: i) the meteoric origin of spring water and their long (more than 50 years) residence time at depth, ii) a positive water balance, ranging between 2 and 4 millions of m3/yr, and iii) a conservative geothermal reservoir volume of about 39km3, iv) a geothermal potential with Er=5.6*1018J and Ef=0.8*1018J. © 2014 Elsevier Ltd.